2017
DOI: 10.31123/akil.437175
|View full text |Cite
|
Sign up to set email alerts
|

Türk Televizyonlarında Yayınlanan Gündüz Kuşağı Programlarında Mahremiyetin Dönüşümü

Abstract: Mahremiyetin, günümüz televizyon programlarında oluşturulan yapay özel alan algısı ile ifşa edildiği ve televizyon programlarının içeriği ile birlikte kavramın alımlamasının da dönüşüm geçirdiği savından yola çıkan çalışmanın ilk bölümünde, mahremiyet kavramını tanımlamak üzere literatür taraması yapılmış ve kavramın göreceliliği bir kez daha onanmıştır. İkinci bölümde televizyon programları başlığı altında, televizyon izlemenin izleyici için neden bir ihtiyaç olduğu sorusuna yönelik kuramlardan bahsedilmiş ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…They also claim that, magazine programs violate the private life of people, and that this negatively affects individuals. Serttaş (2017) found that television characters disclose their privacy for psychological reasons such as being fame, feeling alone, the need to be approved, family problems, childhood and adulthood period without love, as well as some sociological reasons such as finding a job, finding accommodation, and being involved in the media sector.…”
Section: Discussionmentioning
confidence: 99%
“…They also claim that, magazine programs violate the private life of people, and that this negatively affects individuals. Serttaş (2017) found that television characters disclose their privacy for psychological reasons such as being fame, feeling alone, the need to be approved, family problems, childhood and adulthood period without love, as well as some sociological reasons such as finding a job, finding accommodation, and being involved in the media sector.…”
Section: Discussionmentioning
confidence: 99%